A reforma do estado e suas implicações para a gestão escolar: um estudo na rede pública municipal de ensino de Cascavel – PR (2004-2012) - Zoia, Getânia Fátima (2014)
This research aims to analyze the conception of School Management implemented by the Municipal Department of Education (SEMED) in Cascavel, in the municipal public schools in Cascavel – PR, between the years of 2004 and 2012. For this, we undertook the analysis of the documents issued by the SEMED for the schools, contemplating minutes, official letters, laws, decrees, ordinances, terms of agreement, manuals, opinions, reports and technical guidance. We sought to contextualize the implications of the Brazilian State reform, from the introduction of a new management model, the public administration managerial, however, considering the disputes engendered by the different interests, latent the antagonistic classes, which take place in the social policies, now focusing, particularly, the educational policy. Through bibliographical study, initially, we investigated, through the relationships that establish among the State, society and education, the economic, political, social and ideological context inherent to the capitalism restructuring process, outlined at the end of the 20th century, in worldwide, that imposes new forms of control and management. We articulated to this context the conditions that consubstantiated the Brazilian state reform, in the 1990s, unleashed as one of the requirements of the neoliberalism and globalization. Then we intended to understand the propositions that characterized the Basic Education reform, as well as its implications for the Brazilian School Management, aggregated to some of the different meanings adopted by the decentralization concepts, participation and autonomy. Such propositions are understood as part of the materialization of the Brazilian State reform, closely imbricated to the implementation process of the neoliberalism and the globalization, established through guidance from international organizations. Finally, we sought to verify, from the analysis of the documents, which step the referrals of SEMED, directed to the field of School Management, incorporated, materialized or opposed the national proposals recommended for the School Management. The articulation and confrontation between the universal and the particular context allowed the grasp the concept of School Management present in the referrals of SEMED for the municipal public schools in Cascavel – PR, in the facing actions, programs and projects of initiative of the Federal Government. This view shows, above all, that the challenges posed and that run through the effectuation of the education principles on benefit of the working class, far from being achieved, constitute yet, and increasingly, in dispute elements.